2004
DOI: 10.1007/s11137-005-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of technogenic radionuclides in alluvial sediments and among fractions of the soil in the near zone of the krasnoyarsk mining and chemical combine

Abstract: Distribution of technogenic radionuclides in the landscape of the Berezovyi Isl. (Yenisei River) is studied. The observed variations in the density of radioactive contamination are associated with nonuniform lithologic composition of soil-forming rocks and also with different duration of the flooding periods. Radionuclide distribution in alluvial sediments and among fractions of the soil in the region of the Balchug settlement is analyzed, making emphasis on the contribution of the clay fraction to accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Distribution of technogenic radionuclides in the Yenisey floodplain soils has been partly discussed in a number of our publications (Linnik et al, 2004a;Volosov et al, 2004Volosov et al, , 2006Volosov et al, , 2011.…”
Section: Concentration Of Radionuclides In Soil Aggregates (Dry-sifting)mentioning
confidence: 98%
See 1 more Smart Citation
“…Distribution of technogenic radionuclides in the Yenisey floodplain soils has been partly discussed in a number of our publications (Linnik et al, 2004a;Volosov et al, 2004Volosov et al, , 2006Volosov et al, , 2011.…”
Section: Concentration Of Radionuclides In Soil Aggregates (Dry-sifting)mentioning
confidence: 98%
“…Many studies were devoted to measurements and experimental evaluations of radionuclides in soils and sediments at different locations on the Yenisey floodplain (Bolsunovsky et al, 2002;Kuznetsov et al, 1994;Nosov and Martynova, 1996;Nosov et al, 1993;Standring et al, 2009;Sukhorukov et al, 2004;Vakulovsky et al, 1995). It was shown that radionuclides from Krasnoyarsk could migrate as far as the Yenisey delta and estuary but their distribution in floodplain areas was significantly heterogenous due to lithology, geomorphology, vegetation of local landscapes (Linnik et al, 2000) and the hydrological regime in the periods of radionuclide discharges (Linnik et al, 2004a(Linnik et al, , 2004b(Linnik et al, , 2005Nosov et al, 1993). Particular attention was paid to the fact that up to 50% of 137 Cs and more than 60% of 60 Co and 152,154 Eu were transported in suspended material (Kuznetsov et al, 1994;Vakulovsky et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The environmental disasters at nuclear power plants (Chernobyl, Fukushima) activated the assessment of the migration of radionuclides in the environment, the creation of special GIS, tracking and monitoring systems, as well as the creation of a theory of the behavior of radionuclides (the concept of patterns) (Linnik, 2018). Now biogeochemical provinces are classified from their genesis patterns (e.g., natural, natural & technogenic or technogenic), space scope (regional, subregional, zonal or azonal), their evolutionary processes, biological reactions or ecological status.…”
Section: Figure 4 Basic Biogeochemical Taxons Of the Biosphere 0-v -T...mentioning
confidence: 99%
“…The possibility of radioactive contamination of the river bed pebbles, including those underlying alluvial soils and bottom sediments, practically is not taken into account. Moreover, it is considered, that they are not contaminated by TRN because of their transit properties in relation to sandy and sandy-argillaceous bottom sediments [7]. However, still it was noticed by Nosov, etc [1], total activity of all TRN in the river pebbles in the near-field influence zone of the KMCC had not exceeded 40 kBq/m 2 .…”
Section: Introductionmentioning
confidence: 97%